What Have We Learned (or Expect to) From Analysis of Murine Genetic Models Related to Substance Use Disorders? - Peltz, Gary; Tan, Yalun (Frontiers in Psychiatry, 2022)
The tremendous public health problem created by substance use disorders (SUDs) presents a major opportunity for mouse genetics. Inbred mouse strains exhibit substantial and heritable differences in their responses to drugs of abuse (DOA) and in many of the behaviors associated with susceptibility to SUD. Therefore, genetic discoveries emerging from analysis of murine genetic models can provide critically needed insight into the neurobiological effects of DOA, and can reveal how genetic factors affect susceptibility drug addiction. There are already indications that murine genetic models can provide actionable information that can lead to new approaches for alleviating SUDs. However, to optimize the chance that impactful genetic discoveries will emerge, it is essential to carefully consider the type of mouse genetic models that will be analyzed, and to use optimal methods for performing the genetic analysis.